2011
DOI: 10.4254/wjh.v3.i8.219
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive predictors for liver fibrosis in patients with nonalcoholic steatohepatitis

Abstract: AIM:To evaluate certain anthropometric, clinical and laboratory features indicating liver fibrosis in nonalcoholic steatohepatitis and to establish the noninvasive markers for liver fibrosis. METHODS:Eighty-one patients (40 male, 41 female) who were diagnosed with fatty liver by ultrasonographic examination and fulfilled the inclusion criteria participated in the study. Anamnesis, anthropometric, clinical and laboratory features of all cases were recorded and then liver biopsy was performed after obtaining pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
12
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 67 publications
4
12
1
Order By: Relevance
“…Assessment of the different clinical parameters analyzed in this population, such as gender, BMI, waist circumference, glucose intolerance, diabetes and metabolic syndrome, failed to identify the presence of liver fibrosis or steatohepatitis. These parameters were found in similar proportions in all the groups, as reported in other studies (35). Only patient age varied significantly, as patients with more advanced disease stage were older.…”
Section: Discussionsupporting
confidence: 88%
“…Assessment of the different clinical parameters analyzed in this population, such as gender, BMI, waist circumference, glucose intolerance, diabetes and metabolic syndrome, failed to identify the presence of liver fibrosis or steatohepatitis. These parameters were found in similar proportions in all the groups, as reported in other studies (35). Only patient age varied significantly, as patients with more advanced disease stage were older.…”
Section: Discussionsupporting
confidence: 88%
“…However, other authors have reported no significant difference in these parameters [35]. This may be partly due to the different sizes of patient cohorts.…”
Section: Discussionmentioning
confidence: 38%
“…In contrast to the current study results, recent studies expressed that ALT and AST were not reliable markers for NASH or fibrosis (41). Moreover, Uslusoy et al found no relationship between ALT and AST levels, and liver fibrosis (38). In the study by Gholam et al it is observed that except for BMI and hyperglycemia, insulin resistance and the metabolic syndrome were associated with the presence of NASH and fibrosis (42).…”
Section: Discussionmentioning
confidence: 89%
“…Also, disturbed liver function test results had significant association with NASH in several studies (35)(36)(37). Uslusoy et al found no relationship between NASH and BMI (38).…”
Section: Discussionmentioning
confidence: 99%